2015
DOI: 10.1186/s40608-015-0070-4
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between mitochondrial content and bioenergetics with obesity, body composition and fat distribution in healthy older adults

Abstract: BackgroundMitochondrial function declines with age; however, the relationship between adiposity and mitochondrial function among older adults is unclear. This study examined relationships between skeletal muscle mitochondrial content and electron transport chain complex 2 driven respiration with whole body and thigh composition, body fat distribution, and insulin sensitivity in older adults.Methods25 healthy, sedentary, weight-stable men (N = 13) and women (N = 12) >65 years of age, with a BMI range of 18-35 k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
42
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(47 citation statements)
references
References 51 publications
5
42
0
Order By: Relevance
“…This is consistent with recent finding that increased adiposity is associated with decreased mitochondrial function from lower body skeletal muscle biopsies [23].…”
Section: Discussionsupporting
confidence: 93%
“…This is consistent with recent finding that increased adiposity is associated with decreased mitochondrial function from lower body skeletal muscle biopsies [23].…”
Section: Discussionsupporting
confidence: 93%
“…Our study extends previous work showing that mitochondrial respiratory capacity and efficiency energetics were associated with walking speed in older adults . Our data also strengthen recent evidence indicating a positive association between mitochondrial content and insulin sensitivity in older individuals . Taken altogether, these results clearly emphasize the importance of mitochondria for skeletal muscle health and reinforce the view that mitochondria should be considered as important therapeutic targets to prevent or attenuate age‐related deterioration of muscle function and metabolism.…”
Section: Discussionsupporting
confidence: 90%
“…Excess regional adipose tissue may impair skeletal muscle function and reduce mitochondrial density (42, 43); hence, the potential effects of obesity on skeletal muscle mitochondria are important to consider in the interpretation of the present results. While an earlier study has reported that Mfn2 mRNA is decreased in the skeletal muscle of obese individuals (44), a more recent study has shown that protein content of Mfn2 is unaffected (45).…”
Section: Discussionmentioning
confidence: 99%